Waters War on the Cards: Unflinching Rivalry between India & Pakistan shapes New Phase of Enmity - Muhammad Bilal Shafique (Journal of Political Studies, 2020)
This research aims to investigate the lurking perils of war between two nuclear ark rival countries of Pakistan & India on the issue of water. This research has explored that water is the main warfare strategical & psychological tack often used by India against Pakistan. The researcher employed qualitative methodology for the research underhand and adopted thematic analysis as research method for this study. The researcher analysed different research studies related to the issue and considered cases to the research-based statements of the individuals in power from both sides of the countries on the issue of water. The findings of the study revealed that the political individuals and uniformed personnel occupying key positions on Indian side used the threat of water as warfare tactic to achieve political gains specially to win the elections. The findings further concluded that Indian side aggressively treated Pakistani side while gratifying the hatred feelings of Indian elites converting to the feelings of masses through moulding the agenda of mass media. The findings showed that the masses on both sides of the regional countries desire sustainable global peace through consultative dialogue on tables. The study concluded with the recommendations that all issues including Indian Held Kashmir, terrorism, water crisis and other regional issues can be resolved through dialogue. The study may also open new avenues for future researchers.